The Development of Zakat Management in the Digital Age: A Literature Review - Afif Sabil; Hilmi Ridho; Khoirul Anwar; Aizat Khairi (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2025)
The purpose of this study is to determine the development of zakat management in Muslim-majority countries, both in terms of collection and distribution. In addition, it aims to determine the renewal of zakat fiqh in Indonesia and digital-based zakat management. This study includes a literature review that discusses several previous studies related to the development and transformation of zakat management in the digital era using a qualitative approach. The inclusion keywords used to find relevant research themes are “Zakat Management in Islamic Countries,” “Renewal of Fiqh Zakat,” “Interpretation of the Meaning of Mustahik,” “Development of Zakat Objects,” “Determination of Professional Zakat,” “Reinterpretation of Ghārimīn, Sabīlillah, and Riqāb,” and “Digital-Based Zakat Management.” This mapping aims to build a strong theoretical foundation, identify research gaps, avoid duplication, and provide a comprehensive overview of the transformation of zakat management. The results of this study show that the development of zakat in several Islamic countries continues to transform over time, marked by the renewal of nisab and zakat rates, the establishment of zakat institutions, the development of zakat objects, and the expansion of zakat distribution for the public interest that contains values of goodness. The renewal of zakat fiqh in Indonesia is marked by the establishment of professional zakat and the obligation of zakat on paper money as part of the development of zakat objects. Meanwhile, the contextualization of the meaning of mustahik refers to the social conditions of Indonesian society in the modern era. Digital-based management is implemented to adapt to advances in technology and information, which have become a trend among the community. This kind of adaptation in zakat management must be recognized as part of social change. This study highlights the importance of renewing zakat fiqh and digital-based management in the era of society 5.0 for zakat institutions in Islamic countries.